2011
DOI: 10.1007/s11738-010-0697-1
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of sample extraction methods for proteomic analysis of coniferous seeds

Abstract: In this study, three methods of protein extraction from the seeds of the Chinese fir were compared by examining the quality (including the number of protein spots observed) in the two-dimensional gel electrophoresis (2-DE), obtained by isoelectric focusing and sodium dodecyl sulfate polyacrylamide gel electrophoresis of the total released protein. Three protein extraction methods were: TCA-acetone precipitation, SDS extraction/acetone precipitation, and phenol extraction methanol/ammonium acetate precipitation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
12
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 20 publications
1
12
0
Order By: Relevance
“…Then, TCA-acetone was used for protein precipitation, and ice-cold acetone was used to wash the protein pellet. This nding is similar to those of previous reports on coniferous seeds, 36 although it is not exactly the same compared with reports on banana 8 and tomato pollen. The proper extension of the extraction time and increase in the volume of leaching solution will help to enhance the output of proteins.…”
Section: Resultssupporting
confidence: 90%
“…Then, TCA-acetone was used for protein precipitation, and ice-cold acetone was used to wash the protein pellet. This nding is similar to those of previous reports on coniferous seeds, 36 although it is not exactly the same compared with reports on banana 8 and tomato pollen. The proper extension of the extraction time and increase in the volume of leaching solution will help to enhance the output of proteins.…”
Section: Resultssupporting
confidence: 90%
“…Over the last few decades, rapid advancements in high-resolution protein separation, mass spectrometry techniques and bioinformatics knowledge have led to an increasing application of proteomics to elucidate the underlying biology mechanisms [1]. Now, proteomics approaches 3 integrated two-dimensional electrophoresis (2-DE) with mass spectrometry (MS) has still proved to be the predominant technique [2][3][4][5][6][7][8], which was widely used in comparative proteomics studies, posttranslational modifications and protein interaction network analysis [9][10][11].…”
Section: Introductionmentioning
confidence: 99%
“…The perfect protocol of protein extraction should reproducibly capture all most unprejudiced and comprehensive proteins from various tissues of different species while reducing contamination and minimizing degradation and modification. However, considering the diversity and specificity of sample tissues or species, no general and high-efficiency extraction protocol can capture the full proteome [1,10,11]. To date, tremendous efforts are more devoted to developing sample preparation protocols that could enhance plant proteomic analysis [14][15][16][17].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Some researchers also demonstrated that trichloroacetic acid−acetone (TCA−acetone) precipitation gave the highest yield of total protein and the greatest number of protein spots for the following two-dimensional gel electrophoresis (2-DE) analysis. 10 However, protein functional properties are greatly dependent upon their preparation processes, which may affect protein structure along with amino acid composition. For example, protein three-dimensional (3D) structures as well as protein functionalities undergo a significant change during isoelectric precipitation.…”
Section: ■ Introductionmentioning
confidence: 99%